(untitled) (Ameghiniana, 2014)
"Cyclopygid trilobites are described for the first time from the southem hemisphere, extending significatively their palaeogeographic distribution. Degamellafamatinensis n. sp. and Cyclopyge? sp. are described herein from the Ordovician Volcancito Formation (Portezuelo de la Alumbrera, Famatina System). Sedimentologic and morphologic analysis support an outer shelf pelagic habit for these forms. The Volcancito Formation has been traditionally regarded as Early Tremadocian However, the presence of cyclopygids and the associated fauna suggest a Late Tremadocian age for these fossiliferous beds. Accordingly, the stratigraphic range of the Volcancito Formation should be reconsidered."